Gestão financeira das agências reguladoras estaduais multissetoriais: análise, perspectiva e desafios - Negreiros, Josiany Melo (2014)
In a context of administrative reforms to public administration, Brazil underwent changes in the 1990s with the objective of reducing red tape and of approximating the public management to the standards of the private sector. For more efficient management, it was necessary the downsizing of public administration, transferring to the private sector activities that could be controlled by the market. Thus, several utilities concessionaires were privatized, and regulatory agencies were created to ensure the quality of their services. To fulfill this mission, the agencies should be provided with administrative and financial autonomy, exempting therefore political interference in their activities. Thus, noting the need for financial autonomy and the consequent self-sufficiency of resources that should be granted to independent regulatory agencies, this study aimed to analyze the multisectoral state regulatory agencies under the financial perspective in the light of the proposed model in the literature and the expected evolution of the reality of regulation in Brazil. For this analysis, we used bibliographical research and field survey with the application in 19 state agencies. After grouped, summarized and compared with the applied literature, the survey results identified the lack of financial autonomy for state agencies in most cases, be it related to the need of resources or freedom to manage their allocation. In this sense, 88% of the agencies that took the survey found that the bureaucracy itself and the barriers created by their state governments are the major obstacles to the implementation of its resources. Moreover, it was observed that some state agencies have evolved institutionally and that there are still many challenges to overcome.